(untitled) (Malaysian Journal of Learning and Instruction, 2019)
Purpose - The purpose of this experimental study is to investigate the impact of teaching Oriental Music using Blended Learning (BL) approach for the students of senior secondary level in Sri Lanka specifically focusing on their achievement on required competencies of Oriental Music at Ordinary Level. The study analyzes the academic performance of students with detailed comparison of BL environment and traditional learning environment. Authors propose the application of BL approach to teach Oriental Music and study its impact on improvement of students’ competency. The study conducted with the application of a mixed instructional design model of objectivist and constructivist approaches for the design of the blended learning course in a student centred learning environment. Methodology - The study was directed by using true experimental study design with pretest and posttest control groups. BL was applied to the experimental group and the traditional instruction method was applied to control group. 9 schools from Colombo district were randomly selected for the experimental and control groups covering all the three existing school types of Sri Lanka. The study group consisted of 360 students of Grade 10 and Grade 11 who has been studying Oriental Music as a subject for General Certificate of Education Ordinary Level. To analyze the data Descriptive statistics, Paired samples t test, Independent samples t test were utilized. Findings - The findings of the experiment indicated that students who has studied Oriental Music under BL strategy showed a significant improvement in their music academic performances after the intervention. The mean post-test of the experimental group was 71.75 which is significantly higher than the mean control group which was 52.07. The mean difference was 19.68 1.91. Hence, there is a statistically significant increase in the performance of students who studied Oriental Music under blended learning. Thus, it is clearly evident that the blended instruction was effective. Significance - This study indicated a positive platform to mould and cater the entire teaching learning process by introducing BL strategy to Sri Lankan secondary education system and fulfilled an existing research gap by utilizing BL to teach highly traditional abstract art. Results of the study contributes to the curriculum designing field with novel ideas to adapt blended instructions to teach secondary level students effectively.